Guided Growth of Horizontal ZnSe Nanowires and their Integration into High‐Performance Blue–UV Photodetectors. (26th May 2015) - Oksenberg, Eitan; Popovitz‐Biro, Ronit; Rechav, Katya; Joselevich, Ernesto
<x xml:space="preserve">Abstract</x> Perfectly aligned horizontal ZnSe nanowires are obtained by guided growth, and easily integrated into high‐performance blue–UV photodetectors. Their crystal phase and crystallographic orientation are controlled by the epitaxial relations with six different sapphire planes. Guided growth paves the way for the large‐scale integration of nanowires into optoelectronic devices.